Law in Times of the Pandemic - Szymaniec, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The essay tries to show that the legal response to a new threat, such as an unknown disease, is an outcome of many factors, including social attitudes and public sentiment. This is demonstrated by the example of regulations adopted in the 19th century during the cholera epidemic. Similarly, restrictions are now being introduced, modified or mitigated not only under the influence of the threat itself (only partially known), but also of economic factors and social moods. Strengthening the executive branch and increasing the role of legal acts issued by this branch is a common phenomenon in the present situation. By itself, it does not threaten the rule of law yet and enables a quick reaction to a changing situation. However, excessively oppressive restrictions, in some way reversing the modern paradigm of thinking about individual rights, could be such a threat.